Compact eight-antenna array in the smartphone for the 3.5-GHz LTE 8 × 8 MIMO operation - Jun-Yu Lu; Kin-Lu Wong; Wei-Yu Li (2016 IEEE 5th Asia-Pacific Conference on Antennas and Propagation (APCAP), 2016)
A compact eight-antenna array in the smartphone for the 3.5-GHz band (3400 ~ 3600 MHz) LTE 8 × 8 MIMO operation is presented. The eight-antenna array is formed by two quad-antenna arrays disposed along two long side edges of the system ground plane of the smartphone. The quad-antenna array occupies a small size of 1 × 60 mm 2 . For operating in an 8 × 8 MIMO system, the calculated channel capacity for the eight-antenna array can reach about 37 bps/Hz with 20-dB signal-to-noise ratio (SNR). Detailed results of the eight-antenna array and its MIMO performance are presented.